How country size matters for institutional change: comparing skill formation policies in Germany and Switzerland - Graf, Lukas [Verfasser] (My University, 2021)
„This paper argues that country size can play a crucial role in shaping the type of gradual change observed in collective skill formation systems. Collectively governed dual-apprenticeship training has its base in the industrial and crafts sectors of the economy and builds on the decentralised cooperation of multiple public and private stakeholders. As a result, it tends to be strongly path dependent, which favours gradual over radical forms of change. However, in recent years, dual-apprenticeship training has been increasingly challenged by the rise of the knowledge and service economy and the growing popularity of academic forms of education. In this context, I compare policy responses in Switzerland and Germany, which represent one small and one large collective skill formation system, respectively. The historical-institutionalist analysis finds that the dominant trajectory of change is conversion in Switzerland but layering in Germany, with different implications for the future viability of collective skill formation.“ (author’s abstract; BIBB-Doku)
Keywords: S System beruflicher Bildung; T 1.5 International vergleichende Berufsbildungsforschung; Dienstleistungsgesellschaft; 370; Berufsbildungssystem; Vergleichende Berufsbildungsforschung; Wissensgesellschaft; Dienstleistungsgesellschaft; Akademisierung; Zukunftsperspektive; Berufsbildungspolitik; Schweiz; Bundesrepublik Deutschland